Analysis of Neutrophil/Lymphocyte Ratio and Culture Results on Clinical Severity of Patients with CAP - Nurul Afiah; Irda Handayani; Nursin Abd. Kadir (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Community-Acquired Pneumonia (CAP) is an acute infection with high morbidity and mortality, especially among toddlers and elders in Indonesia. Culture is the gold standard for infectious diseases, which requires a long time. Therefore, a rapid, inexpensive, easy-to-use marker such as NLR is needed. To analyze the relationship of NLR and culture results with the clinical severity of CAP. A retrospective study with a cross-sectional design was performed using secondary data from CAP patients at Dr. Wahidin Sudirohusodo Hospital from January 1st, 2018 to July 31st, 2021. The study conducted on 113 samples showed no significant differences between NLR and clinical severity of CAP (p-value of 0.071). However, the mean value of NLR in severe CAP was higher (6±4.74) than in moderate CAP (2.58±1.8) with no significant correlation (p-value 0.071). There was a significant difference in culture on the clinical severity of CAP (p-value 0.005). A positive correlation was found between culture and clinical severity of CAP (p-value 0.004) with weak correlation strength (r=0.266). NLR is an early detection marker of infection. Stimulation of growth hormone causes an increase in neutrophil count, apoptosis acceleration, and lymphocyte redistribution; therefore, increased neutrophils are common in severe clinical conditions. The insignificant relationship between NLR and clinical severity might be caused by the therapeutic intervention given. The ATS/IDSA guidelines stated that culture results were positive in 4-15%. The mean NLR value in severe CAP was slightly higher than that of moderate CAP, but no significant difference was found. There was a weak correlation between culture results and the clinical severity of CAP patients.